Risk stratification and contributing factors of deep vein thrombosis among patients admitted at Debre Markos comprehensive specialized hospital, Ethiopia in 2024 - Mitiku, Haymanot Zeleke; Assefa Addis, Birtukan; Edmealem, Afework; Tsegaye, Dejen; Biyazin, Yalemgeta; Abate, Abebe (Frontiers in Medicine, 2024)
Introduction: Deep vein thrombosis is a serious condition and most common disease that can lead to significant morbidity and mortality in hospitalized patients. Studies conducted in various hospitals in Ethiopia have reported deep vein thrombosis prevalence rates ranging from approximately 5% to 10% among hospitalized patients. The stratification of deep vein thrombosis risk and identification of associated risk factors are critical for assessing deep vein thrombosis in hospital settings. Well scoring provides valuable frameworks for assessing individual risk. This study aimed to assess the stratification of deep vein thrombosis risk and identify risk factors among patients admitted at Debre Markos Comprehensive Specialized Hospital. Method: A facility-based cross-sectional study was conducted from December 2023 to February 2024. The study included 423 adult patients, and data were collected using a structured questionnaire and chart review. Ordinal logistic regression analysis was conducted after performing model test.Result: The prevalence of deep vein thrombosis was found to be 7.9%, with 44.2% categorized as having no risk, 8.1% as moderate risk, and 47.7% as high-risk for stratification of deep vein thrombosis risk. Various risk factors, such as regular alcohol consumption (odd ratio 4.59, p=.032), a history of previous deep vein thrombosis ((odd ratio 28.32, p=.000), the presence of a central catheter (odd ratio 12.92, p=.000), a severe lipid profile (odd ratio 3.8 p= .001), and a longer duration of stay in the ward (odd ratio 1.28, p= .000), were significantly associated with high-risk for stratification of deep vein thrombosis risk .: The prevalence of high-risk deep vein thrombosis stratification was found to be high, and the occurrence of deep vein thrombosis was high within this risk group. Regular alcohol consumption, a history of previous deep vein thrombosis, the presence of a central catheter, a severe lipid profile, and a longer duration of stay in the ward were statistical significantly for highrisk deep vein thrombosis stratification. The study highlights the importance of identify patients who are high-risk deep vein thrombosis stratification and addressing the stratification of deep vein thrombosis risk factors.